Suffering in silence: consequences of sexual violence within marriage among young women in Nepal - Shah Iqbal; Tamang Jyotsna; Puri Mahesh (BMC, 2011)
Abstract Background Despite the grave consequences of sexual violence, and it's persistence both within and outside marriages, this subject has received relatively little attention from researchers, policy makers, and programme managers in Nepal. This paper explores the definition of sexual violence and its various forms and consequences as reported by young married women in Nepal. In addition, it describes the coping mechanisms used by young married women to avoid sexual violence perpetrated against them by their husbands. Methods This paper analyzes data collected during the qualitative study on "Sexual violence among young couples in Nepal", conducted amongst two major ethnic groups - Brahmin/Chhetri and Tharu - between 2006 and 2007. The data is comprised of 39 free-lists and 15 in-depth case histories with married women aged 15-24 years. The average rank and Smith's Salience were calculated from the free-listing data. The thematic analysis approach was used for the analysis of information from the case histories. Results Approximately three-quarters (74%) of the young women mentioned 'sex against one's wishes' as sexual violence within marriage (SVWM). Sixty-two percent of respondents described 'forced sex during illness' and 'forced sex after consumption of alcohol' as SVWM. About half of young women (48.7%) who participated in the free-listing exercise reported having experienced SVWM. The types of SVWM ranged from unwanted sexual touch to forced sex. Backache, headache, lower abdominal pain, vaginal bleeding and thoughts of suicide were the most commonly reported negative physical and psychological health consequences of SVWM. Women reported various coping strategies including 'trying to convince husbands', 'sleeping in a separate room', 'visiting maternal home', 'waking up the children', and 'using pretexts such as being ill or menstruating', to avoid SVWM. However, in most cases, women reported that these coping strategies were unsuccessful. Almost all women experiencing SVWM were socially isolated and did not turn to institutions, relatives or friends for advice and support. Conclusions Sexual violence within marriage is common in Nepal. Findings provide circumstantial evidence of links between sexual violence and negative general and reproductive health outcomes for women. Various actions are required to prevent SVWM and provide immediate support to the victims.